2018
DOI: 10.1097/mcc.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory processes during acute respiratory distress syndrome: a complex system

Abstract: We suggest that therapeutic interventions in ARDS should be based on a systems approach to inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…Acute respiratory distress syndrome (ARDS) is characterized by increased lung permeability, pulmonary oedema and diffuse inflammation, which lead to disruption of alveolar capillary membranes [1]. Many studies have indicated that excessive activation of multiple inflammatory cell types and release of inflammatory mediators play vital roles in the development of ARDS [2,3]. Among these cell types, CD4+ T cells play an important role in the pathogenesis of ARDS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory distress syndrome (ARDS) is characterized by increased lung permeability, pulmonary oedema and diffuse inflammation, which lead to disruption of alveolar capillary membranes [1]. Many studies have indicated that excessive activation of multiple inflammatory cell types and release of inflammatory mediators play vital roles in the development of ARDS [2,3]. Among these cell types, CD4+ T cells play an important role in the pathogenesis of ARDS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulated Alveolar Epithelial Cells. Excessive lung inflammation is a proverbial feature of sepsis-related ALI/ARDS [6,18]. Therefore, we elucidated the roles of NEAT1 in LPS-induced inflammation in AECs.…”
Section: Neat1 Knockdown Suppressed Inflammation In Lps-mentioning
confidence: 98%
“…For example, AEC lesions disrupt cellular integrity and the ability to clear fluid from the alveolar space, clinically translating into lung edema. Intriguingly, recent studies also have defined ALI/ARDS as a syndrome of diffuse inflammatory lung injury [5,6]. During ALI/ARDS, AECs participate in the inflammatory response by acting as major sources of inflammatory cytokines (e.g., IL-1β, IL-6) and chemokines (e.g., MCP-1, IL-8).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the invading pathogens, immunological mechanisms are activated. Some scholars have described the inflammation induced by the immune response as disease-related network, in which several pathogen-derived components of innate immunity interact nonlinearly [26]. The activation of antigen-presenting cells (APCs) includes the up-regulation of monocytes, macrophages, dendritic cells and endothelial cells.…”
Section: At the Cellular Level Sepsis-induced Inflammatory Cells Dammentioning
confidence: 99%